Discovery of the first resolved triple white dwarf. Issue 1 (22nd November 2018) - Perpinyà-Vallès, M; Rebassa-Mansergas, A; Gänsicke, B T; Toonen, S; Hermes, J J; Gentile Fusillo, N P; Tremblay, P-E
Abstract: We report the discovery of J1953–1019, the first resolved triple white dwarf system. The triplet consists of an inner white dwarf binary and a wider companion. Using Gaia DR2 photometry and astrometry combined with our follow-up spectroscopy, we derive effective temperatures, surface gravities, masses, and cooling ages of the three components. All three white dwarfs have pure-hydrogen (DA) atmospheres, masses of $0.60\hbox{--}0.63\, \mbox{$M_{\odot }$}$, and cooling ages of 40–290 Myr. We adopt eight initial-to-final mass relations to estimate the main-sequence progenitor masses (which we find to be similar for the three components, 1.6–2.6 M⊙ ) and lifetimes. The differences between the derived cooling times and main sequence lifetimes agree for most of the adopted initial-to-final mass relations, hence the three white dwarfs in J1953–1019 are consistent with coeval evolution. Furthermore, we calculate the projected orbital separations of the inner white dwarf binary (303.25 ± 0.01 au) and of the centre of mass of the inner binary and the outer companion ($6398.97± 0.09$ au). From these values, and taking into account a wide range of possible configurations for the triplet to be currently dynamically stable, we analyse the future evolution of the system. We find that a collision between the two inner white dwarfs due to Lidov–Kozai oscillations is unlikely, though if it occurs it could result in a sub-Chandrasekhar Type Ia supernova explosion.